Perancangan User Interface Aplikasi Aritmatika Tingkat Rendah Menggunakan Metode Design Thinking - Miladia Nurunnisa; Nadila Puspita Nuryadi; Sinta Solihat (STMIK Sumedang, 2022)
Arithmetic is a material in mathematics, which includes learning basic operations such as addition, subtraction, multiplication, and division. Mathematics is a subject that has various levels of difficulty from low to high. The way of delivery in learning also affects student learning outcomes, if the teacher can convey mathematical material well, students will find it easy to work on problems or digest the material provided. To increase students' interest in arithmetic, a learning media is designed that can support learning, and increase student interest in low-level arithmetic learning. The learning media designed are in the form of